Hubungan Komponen Quality of Work Life dengan Motivasi Kerja Perawat di Puskesmas Wera Kab. Bima NTB - Nismawati Nismawati (Universitas Ahmad Dahlan, 2019)
This study aims to see determine the components of the quality of work-life associated with the work motivation of nurses in Puskesmas Wera. The quality of work-life components that are have been investigated is that the facilities available, occupational health and safety, employee involvement, balanced compensation, communication, career development, problem-solving, the safety of labor , and pride in institutions. This research is could be a quantitative research employing a cross-sectional approach. Sampling amounting to 40 respondents, with a compplete sampling method. Bivariate analysis was obtained based on the results of research conducted by nurses who have low work motivation as much as 14 (35% ) and nurses who have high work motivation as much as 26 (65% ). Components of quality of work life related to work motivation are available facilities, employee engagement, balanced compensation, communication, problem solving, job security and pride in the institution.